Integrasi Maslahah Ibnu Qayyim dalam Etika Green Economy pada Era 5.0 - Muhammad Faujan Al Hadi; Lina Marlina Susana (AL-Ikhtiar : Jurnal Studi Islam, 2026)
This study aims to analyze the integration of the maslahah concept according to Ibn Qayyim as the basis of economic ethics in the development of the Green Economy in the 5.0 era. The 5.0 era is characterized by the use of intelligent technology oriented towards improving the quality of human life, so an ethical framework is needed to ensure that economic activities run sustainably. Through a qualitative approach based on literature review, this study examines the relevance of maslahah values ​​to the principles of the green economy, such as production efficiency, responsible resource management, sustainable investment, and equitable distribution of economic benefits. The results of the study show that Ibn Qayyim's maslahah provides a normative orientation for economic activities so that they do not only pursue short-term profits, but also consider the long-term impacts on ecological balance and public welfare. The concept of dar' al-mafasid emphasizes the need to prevent environmentally damaging economic practices, while jalb al-mashalih encourages innovation and investment in green sectors such as renewable energy and the circular economy. The integration of these two concepts can strengthen the implementation of the Green Economy in the 5.0 era so that it is more adaptive, ethical, and in accordance with the principles of sustainable development (SDGs) from an Islamic economic perspective. Abstrak Penelitian ini bertujuan untuk menganalisis integrasi konsep maslahah menurut Ibnu Qayyim sebagai dasar etika ekonomi dalam pengembangan Green Economy pada era 5.0. Era 5.0 ditandai dengan pemanfaatan teknologi cerdas yang berorientasi pada peningkatan kualitas hidup manusia, sehingga diperlukan kerangka etis untuk memastikan aktivitas ekonomi berjalan secara berkelanjutan. Melalui pendekatan kualitatif berbasis kajian literatur, penelitian ini menelaah relevansi nilai maslahah terhadap prinsip-prinsip ekonomi hijau, seperti efisiensi produksi, pengelolaan sumber daya yang bertanggung jawab, investasi berkelanjutan, dan distribusi manfaat ekonomi yang berkeadilan. Hasil kajian menunjukkan bahwa maslahah Ibnu Qayyim memberikan orientasi normatif bagi aktivitas ekonomi agar tidak hanya mengejar keuntungan jangka pendek, tetapi juga mempertimbangkan dampak jangka panjang terhadap keseimbangan ekologi dan kemaslahatan publik. Konsep dar’ al-mafasid menekankan perlunya mencegah praktik ekonomi yang merusak lingkungan, sementara jalb al-mashalih mendorong inovasi dan investasi pada sektor-sektor hijau seperti energi terbarukan, dan ekonomi sirkular. Integrasi kedua konsep ini dapat memperkuat implementasi Green Economy pada era 5.0 sehingga lebih adaptif, etis, dan sesuai dengan prinsip pembangunan berkelanjutan (SDGs) dalam perspektif ekonomi Islam..